Association between post-stroke depressiveness and the utilization of healthcare services three months after the stroke - Raphaela Artner; Christine Meisinger; Michael Ertl; Markus Naumann; Jakob Linseisen; Timo Schmitz (Scientific Reports)
Abstract Post-stroke depression affects approximately one-third of stroke survivors and can result in various adverse outcomes. With the rising prevalence of strokes, understanding the impact of post-stroke depression on healthcare utilization is crucial. The study examined the association between patient-reported post-stroke depressiveness and the healthcare service utilization three months post-stroke. The prospective Stroke Cohort Augsburg (SCHANA) study assessed post-stroke depressiveness using the Patient Health Questionnaire (PHQ-9) during hospital stay. Participants reported their utilization of medical and therapeutic services, rehabilitation, and inpatient hospital stays three months post-discharge. Multivariable adjusted linear and binary logistic regression analyses examined the association between post-stroke depressiveness and healthcare service utilization. Among 546 participants included into the analyses, 57.1% had no depression, 28.8% had mild depression and 14.9% had moderate to severe depression. Higher PHQ-9 scores were associated with a significantly increased likelihood of inpatient hospital treatment (OR = 1.07; 95% CI: 1.01–1.14; p = 0.016), attendance at rehabilitation programs (OR = 1.09; 95% CI: 1.03–1.15; p = 0.003), and more frequent utilization of general practitioners/internists (beta = 0.10; 95% CI: 0.01–0.19; p = 0.036). In conclusion, post-stroke depressiveness was associated with increased healthcare service utilization. Further studies are required to gain a more comprehensive understanding.